A Case of Hemophagocytic Lymphohistiocytosis following Refractory Kawasaki Disease - Li, Ye; Wang, Yulong; Li, Shen; Liu, Mingjing; Wang, Dingding; Xu, Chaoyue; Zhang, Luan (Klinische Pädiatrie, 2020)
Hemophagocytic lymphohistiocytosis (HLH) is a systemic inflammatory disorder characterized by uncontrolled histiocytic proliferation, hemophagocytosis, macrophage activation, and up-regulation of inflammatory cytokines (Grom AA., Current opinion in rheumatology 2003; 15: 587–590). HLH is usually divided into two types: primary (familial) HLH and secondary (reactive) HLH. Primary HLH is associated with primary immune deficiencies in which specific gene mutations play an important role, such as perforin defects.